PERTANGGUNGJAWABAN HUKUM TERHADAP KEJAHATAN CYBER DALAM DOMPET DIGITAL DI ERA FINTECH PADA APLIKASI DANA - Raymond, Raymond Marhehetua Hutahaean; Gumilar, Ridho Waridan; Maulana, F. Rizky; Al' Daffa, M. Arysa; Sjofjan, Lindryani (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2025)
The rapid development of information technology has driven the transformation of financial systems into more digital forms through innovations in financial technology (fintech). One of the most popular fintech products in Indonesia is digital wallets, such as the DANA application. However, the convenience of digital transactions also creates vulnerabilities to cybercrime, which can harm users. This study aims to analyze the legal liability for cybercrime in the use of the DANA digital wallet, as well as to evaluate the effectiveness of existing regulations in protecting consumers. The research method used is normative juridical, with a statutory and case study approach. Data were obtained through literature review, documentation, and analysis of cybercrime cases involving the DANA application. The results of the study indicate that perpetrators of cybercrime involving digital wallets can be sanctioned under the Law on Electronic Information and Transactions (ITE Law), the Consumer Protection Law, and other relevant regulations. However, there are still weaknesses in law enforcement, particularly in tracking down perpetrators and providing compensation to victims. In addition, digital wallet providers are also responsible for enhancing their security systems and ensuring transparency in user data protection. In conclusion, legal accountability for cybercrime in digital wallets is not yet fully effective, and synergy between regulators, law enforcement agencies, and fintech industry players is needed to create a secure and trustworthy digital financial ecosystem. Keywords: Cybercrime, Digital Wallet, Legal Liability